2017
DOI: 10.1093/heapol/czx098
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers of kangaroo mother care implementation from a health systems perspective: a systematic review

Abstract: Kangaroo Mother Care (KMC) is an evidence-based intervention that reduces neonatal morbidity and mortality. However, adoption among health systems has varied. Understanding the interaction between health system functions—leadership, financing, healthcare workers (HCWs), technologies, information and research, and service delivery—and KMC is essential to understanding KMC adoption. We present a systematic review of the barriers and enablers of KMC implementation from the perspective of health systems, with a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(168 citation statements)
references
References 42 publications
5
139
0
4
Order By: Relevance
“…When deficiencies in practice were identified, lack of knowledge was often a contributing factor (Higman, Wallace, Law, Bartle, & Blake, ). A recent systematic review showed that lack of professional education and training was one of the major barriers for nurses to initiate neonatal care (Chan, Bergelson, Smith, Skotnes, & Wall, ). Nursing staff are important advocates in the utilisation of neonatal care intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When deficiencies in practice were identified, lack of knowledge was often a contributing factor (Higman, Wallace, Law, Bartle, & Blake, ). A recent systematic review showed that lack of professional education and training was one of the major barriers for nurses to initiate neonatal care (Chan, Bergelson, Smith, Skotnes, & Wall, ). Nursing staff are important advocates in the utilisation of neonatal care intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Chan, Bergelson, Smith, Skotnes, & Wall, 2017). Nursing staff are important advocates in the utilisation of neonatal care intervention.…”
mentioning
confidence: 99%
“…KMC was also found to increase infant growth (Bera et al, 2014;Lumbanraja, 2016), breast feeding (Conde-Agudelo & Díaz-Rossello, 2016; Luong, Nguyen, Thi, Carrara, & Bergman, 2016), mother-infant attachment (Boundy et al, 2016;Cho et al, 2016;Conde-Agudelo & Díaz-Rossello, 2016;Feldman, Rosenthal, & Eidelman, 2014), and infant neurodevelopment (Akbari et al, 2018;Charpak et al, 2017). Despite the strong evidence and establishment of KMC Centers of Excellence in many countries (Sarfo, 2018), significant barriers to implementation persist at all levels: organizations, clinical teams and families (Chan, Bergelson, Smith, Skotnes, & Wall, 2017).…”
Section: Kangaroo Mother Carementioning
confidence: 99%
“…Researchers have found that breastfeeding decreases behavioral and physiologic signs of stress in response to painful procedures (Weissman et al, ). Similarly, SSC is an evidence‐based practice that increases physiologic stability (Chi Luong, Long Nguyen, Huynh Thi, Carrara, & Bergman, ), decreases stress responses (Gao et al, ), and improves long‐term neurodevelopment in preterm infants (Feldman et al, ); however, significant organizational barriers and concerns regarding infant toleration of SSC limit nurses’ facilitation of this intervention (Chan, Bergelson, Smith, Skotnes, & Wall, ; Kymre, ). Empirically‐based rationales for the promotion of SSC in the NICU, such as that provided by the NSE model might increase rates of SSC, as educational programs for NICU nurses on the importance of SSC have increased nurses’ competence in facilitating SSC and increased rates of SSC among mothers of preterm infants (Hendricks‐Munoz & Mayers, ).…”
Section: Practice and Research Implicationsmentioning
confidence: 99%
“…Researchers have found that breastfeeding decreases behavioral and physiologic signs of stress in response to painful procedures (Weissman et al, 2009). Similarly, SSC is an evidence-based practice that increases physiologic stability (Chi Luong, Long Nguyen, Huynh Thi, Carrara, & Bergman, 2016), decreases stress responses (Gao et al, 2015), and improves long-term neurodevelopment in preterm infants (Feldman et al, 2014); however, significant organizational barriers and concerns regarding infant toleration of SSC limit nurses' facilitation of this intervention (Chan, Bergelson, Smith, Skotnes, & Wall, 2017;Kymre, 2014 (Keunen, van Elburg, van Bel, & Benders, 2015), may interrupt the causal pathway between stress exposure and neurodevelopmental impairment. However, such interventions require more rigorous testing.…”
Section: Implications For Clinical Practicementioning
confidence: 99%